Fixed Asset Audit of Health Center X by PAF Based on Findings of Depreciation Corrections for Equipment and Machinery - Rohmawati, Indah Puspita; Widodo, Condro (Manunggal Halim Jaya, 2025)
This study examines depreciation corrections as indicators of weaknesses in fixed asset accounting policies within public sector financial reporting. A case study at Community Health Center X employs evidence from the Public Accounting Firm (PAF) audit and recent literature analysis to assess compliance with GASS standards. The findings reveal inconsistencies in recording depreciation and asset disposal, resulting in overstated asset values, distorted depreciation expenses, and delays in asset retirement. These conditions reduce the quality of financial statements, hinder budget efficiency, and potentially affect audit opinions. Key contributing factors include limited human resource capacity, inadequate asset information systems, and the absence of standardized disposal procedures. The study recommends the digitalization of asset management systems, the development of standardized SOPs for asset disposal, regular inventory and reconciliation, and capacity building for financial and asset officers. Implementing these measures is expected to enhance the quality of financial reporting, strengthen public accountability, and improve the legitimacy of local government financial governance.